G103(P) Impact of standards issued by RCPCH on quality of child protection reports: an 8-year review of practice. (May 2019) - Jayaprakash, K; Issa, M; Dominic, M
Abstract : Child protection assessments have been undertaken at district general hospitals for many years. In 2013 the RCPCH updated the Child Protection guidance which covers child protection processes across the whole range of medical and social interactions. Aim: This audit reviewed Child protection Medical Reports against standards provided by the Royal College (RCPCH Child Safeguarding Companion 2013, table 1 ). Our practice over the past 8 years (2010–2017) was evaluated. Measurable and qualitative improvements were assessed. Methods: Child protection reports between 2010–2017 were reviewed (n=288). Equal numbers of random reports were selected per year from all consultants and trainees and assessed against the criteria provided by RCPCH. A scale was designed to assess quality of reports based on a combination of GMC good practice and RCPCH Discussion of Correspondence assessment Outcomes: A total of 288 medical reports of children (between the ages 0–18) were assessed from 2010–2017. There was a steady improvement in all criteria assessed over the years. We performed a regression analysis to test the cause effect of time on the report quality. This indicated that the quality of the reports showed a steady improvement year on year. There was positive effect of time on quality at 95% (statistically significant) from 2014–2017. Conclusion: From this audit we conclude that the quality of reports showed improvement particularly in the last 3 years to which we believe the updated guidance from the RCPCH Companion 2013 contributed.